World trade in health services in a competitive environment and global transformations - Gaponova, Elina (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 2018)
The author analyzes the main directions of international trade in medical services. The issues of increasing the efficiency of health care services and controlling their quality, implementation of international cooperation in health care sphere are considered. Particular attention is paid to existing international trade agreements in the health care sphere